2020
DOI: 10.1002/pa.2275
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and entrepreneurial intention: The mediating role of risk aversion

Abstract: The aim of this paper is to investigate the influence of big five personality traits on entrepreneurial intentions with the mediating role of risk aversion. A structured questionnaire was used and collected data from 274 Pakistani students (university level). The hypotheses were tested through structural equation modeling by using AMOS. The findings display that the personality trait “conscientiousness” has a significant positive influence on entrepreneurial intentions while the traits, extroversion, openness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 78 publications
3
39
1
2
Order By: Relevance
“…Therefore, it may be important for entrepreneurs to nurture long and trustworthy relationships with other stakeholders for successful ventures. Some of the previous studies have reported a negative association between agreeableness and entrepreneurial intentions (Ahmed et al, 2020) but the findings of the study slightly differ. This might be because helpful and cooperative individuals might also reflect intent to get involved in entrepreneurial activities and can also have a successful entrepreneurial career.…”
Section: Discussioncontrasting
confidence: 78%
“…Therefore, it may be important for entrepreneurs to nurture long and trustworthy relationships with other stakeholders for successful ventures. Some of the previous studies have reported a negative association between agreeableness and entrepreneurial intentions (Ahmed et al, 2020) but the findings of the study slightly differ. This might be because helpful and cooperative individuals might also reflect intent to get involved in entrepreneurial activities and can also have a successful entrepreneurial career.…”
Section: Discussioncontrasting
confidence: 78%
“…Table 1 has the following literature, which is based on studies done from 2012 to 2022. Ahmed et al (2022) conducted a study in Pakistan on the influence of the big five personality traits on entrepreneurial intentions. The study found that extroversion, neuroticism, openness to experience and agreeableness do not have a big effect on whether or not someone wants to start their own business.…”
Section: Studies That Delinked Some Characteristics From Entrepreneur...mentioning
confidence: 99%
“…Studies have presented that successful entrepreneurs have similar characteristics to each other (see Timmons et al, 2004;Carland et al, 1984;Desai et al, 2009;Ehigie et al, 2003;Bulu et al, 2005;Hui et al, 2006;Djankov et al, 2007;Papzan et al, 2008;Abdullah et al, 2009;Di Zhang et al, 2011) with some studies arguing that some characteristics presented by other studies do not lead to entrepreneurial success or/and intention (see Ahmed et al, 2019Ahmed et al, , 2022Awwad et al, 2021;Biswas & Verma, 2021a, 2021bSarwoko & Nurfarida, 2021;Mhlanga, 2019;Franco & Prata, 2019;Zhou et al, 2019;Setia, 2018;Djankov et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurial intention is impacted by suitability, the requirement for accomplishment, regard toward oneself, locus of control, emotional demeanor, and association ( Wu et al, 2019 ; Tan et al, 2021 ). Modern analysts have questioned the usefulness of personality measures in anticipating occupation-related criteria, in light of doubtful study results ( Guion and Gottier, 1965 ; Ahmed et al, 2020 ) and are concerned that most personality measures are replicated. Personality traits are a multi-dimensional construct that demonstrate how well workers perform their undertakings, the actions they select, and the skill they demonstrate in tackling issues ( Luc, 2020 ; Shah et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%